Rectifying Students’ Reading Skill Through Visual Auditory Kinesthetic (VAK) Method At English Classroom - Hermansyah, Sam; Hasyuni, Hasyuni; Mansuarni, Mansuarni; Haryanto, Haryanto; Jenni Pannaco, Jenni Pannaco; Jelma, Jelma (La Ogi : English Language Journal, 2022)
ABSTRACTThe goal of this article incourage any improvement in the student reading skill in terms of discuss class after being taught by visual auditory kinesthetic method. With the use of experimental method this research design is quantitative. On September 2020, this research was conducted in two weeks. The subject of this article was english education students college consisting of 20 students in the first semester. Method of collection data was test of pre-test and post-test. Data analysis techniques were calculating jihad’s test multiple choice by 20 question software and the spss statistical method.The result show that: Post test is higher than Pretest's. For Pretest Acquired, score means 74.5. In Post test grew to 90.5. Certainly there is an improvement in students ' reading skill trough visual auditory kinesthetic so that the dominant theory hypothesis is H1 (Alternative Hypothesis).It can be concluded that visual auditory kinesthetic method can improve students college reding skill.